The alternative three factor model : evidence from China - Chua, Victor Kim Loong (2013)
We examine the performance of the Alternative Three-Factor Model of Chen et al. (2011) in China. Conducting regression analysis using monthly returns of 25 portfolios formed by size and book-to-market-equity, we find that the model underperforms CAPM and the Fama-French Three-Factor Model in explaining stock returns based on the alpha and R-squared generated. The investment factor loadings are largely insignificant while the ROE factor loadings show a negative relationship with returns, which is contrary to the new model’s economic intuition. Using the Fama-MacBeth regression, we find that both factors are statistically insignificant in explaining the cross-sectional differences in stock returns.